Adverse events following live-attenuated intranasal influenza vaccination of children with cystic fibrosis: Results from two influenza seasons. Issue 37 (5th September 2017) - Boikos, Constantina; Joseph, Lawrence; Scheifele, David; Lands, Larry C.; De Serres, Gaston; Papenburg, Jesse; Winters, Nicholas; Chilvers, Mark; Quach, Caroline
Abstract: Background: Despite the approved use of live-attenuated intranasal influenza vaccine (LAIV) for seasonal immunization of patients with cystic fibrosis (CF), many questions remain unanswered regarding the timing, duration, and types of adverse events that occur following administration of this vaccine. Methods: In 2012 and 2013, 264 LAIV doses were administered to 198 patients aged 2–19 with CF. Vaccinees were followed prospectively for 55 days after vaccination (day 0) and information on adverse events was collected. Bayesian change-point analysis was used to identify the risk period following LAIV during which participants had a higher risk of reporting adverse events. Multivariable zero-inflated Poisson regression models were then used to estimate the adjusted incidence rate ratio (aIRR) and 95% credible interval (CrI) of reporting each adverse event in the risk period versus the control period. Results: There was a higher risk of reporting serious adverse events (SAEs) (aIRR 1.45, 95% CrI (0.29, 5.17)) and solicited symptoms during days 0–6 of follow-up compared to control period days 7–55. However, most SAEs were not causally related to LAIV and the solicited symptom episodes were brief, usually lasting 1–2 days. There was no increased risk of antibiotic prescriptions for respiratory conditions in the risk vs. control periods (aIRR 0.48, 95% CrI (0.23, 0.91)). Conclusions: Adverse events were most common 0–6 days after LAIV administration but were generally benign and self-limiting. Pulmonary exacerbations did not increase in frequency.